A comparative FTIR study for supplemented agavin as functional food. (June 2020) - Vázquez-Vuelvas, Oscar F.; Chávez-Camacho, Félix A.; Meza-Velázquez, Jorge A.; Mendez-Merino, Emilio; Ríos-Licea, Merab M.; Contreras-Esquivel, Juan Carlos
Abstract: Functional foods are products focused to human consumption with benefits to different physiologic aspects in order to prevent diverse metabolic problems in the body. Prebiotics recently have been started to be employed as functional foods, and fructans as inulin or agave inulin, known as agavin, represent a valuable source of them. Standard polysaccharides as starch, inulin, cellulose and agavin were vibrationally analyzed by FTIR spectroscopy, as well as solid mixtures with different agavin-cellulose and agavin-cocoa ratios, to identify important absorption peaks to detect evolutive changes of bands in absorbance intensities and wavenumbers displacements, in order to employ this information for possible adulteration in this prebiotic functional foods. Three commercial products identified as supplemented agavins with Aloe vera, antioxidants and cocoa were vibrationally analyzed and described by comparative visualization with standard solid mixtures for detecting discrepancies with ingredient compositions. The vibrational patterns displayed by standard polysaccharides allowed to identify frequency zones for making an approach to elucidate standards; furthermore, solid mixtures of standards described the evolution of absorption peaks proportionally to the ratio of the samples. Spectra of agavin-cellulose and agavin-cocoa solid mixtures exhibited an increment in bands associated with C–O and C–O–C between 1176 cm −1 and 1074 cm −1 when the agavin content diminished in the mixture; an opposite behavior was depicted at 926 cm −1 absorption band, intensity decreased when the agavin ratio decreased. The spectra of commercial agavins provided the information to identify structural similarities with the absorption bands shown by polysaccharide standards, which made it possible to identify the presence of the components of interest. Graphical abstract: Image 1 Highlights: FTIR-ATR spectroscopy is a rapid method to identify structure of polysaccharide samples. Vibrational spectra of ingredients may be used to identify adulterations in foods. Agavin and polysaccharides were characterized vibrationally to identify interest peaks. Absorption peaks assignments may be detected to find anomalies in solid mixtures. Commercial supplemented agavins displayed signals identified in the spectra of standards.